Effects of Neurodynamic Mobilizations on Pain Hypersensitivity in Patients With Hand Osteoarthritis Compared to Robotic Assisted Mobilization: A Randomized Controlled Trial - Pedersini, Paolo; Valdes, Kristin; Cantero-Téllez, Raquel; Cleland, Joshua; Bishop, Mark; Villafañe, Jorge Hugo (My University, 2021)
Objective To evaluate the effectiveness of the neurodynamic mobilization techniques compared with passive robotic physiologic movement in patients with hand osteoarthritis (OA). Methods We conducted a randomized controlled trial. A total of 72 patients (mean ± SD age 71 ± 11 years) with dominant symptomatic hand OA were randomized in 2 groups, and both received 12 treatment sessions over 4 weeks. The experimental group received neurodynamic mobilization of the median, radial, and ulnar nerves, and the control group received robotic-assisted passive movement treatment. Both groups also participated in a program of hand stability exercises. Outcome measures included pain intensity, pressure pain thresholds (PPTs), and strength measurements. Group-by-time effects were compared using mixed-model analyses of variance. Results After the intervention, the experimental group had statistically significant, higher PPTs than the control group at the thumb carpometacarpal joint by 0.7 kg/cm2 (95% confidence interval [95% CI] 0.6, 0.8), the median nerve by 0.7 kg/cm2 (95% CI 0.6, 0.7), and the radial nerve by 0.5 kg/cm2 (95% CI 0.3, 0.6); however, the difference was not statistically significant at 3 months postintervention. Although mean values in the experimental group were higher than in the control group at all PPT sites at both assessments, these differences were not statistically significant. The experimental group experienced a statistically significant reduction in pain immediately postintervention, but this was not present at the 3-month follow-up. There were no statistically significant differences in pinch or grip strength between groups. Conclusion We found that neurodynamic mobilizations decreased hypersensitivity in patients with hand OA immediately after the intervention; however, differences were no longer present at 3 months. The results suggest that these techniques may have some limited value in the short term but do not have lasting effects.
Keywords: Dolor - Aspectos fisiológicos; Artrosis; Manos; Robótica; Pain; Hand Osteoarthritis; Robotic Assisted Mobilization; Thumb